Oghuz Khagan as a Strategic Hero - Kocak, Aynur; Zenginoglu, Christina (MILLI FOLKLOR DERGISI, 2018)
Having a special importance in the Turkish cultural history, the legend of Oghuz Khagan (Oguz Kagan in Turkish) has been the center of several studies for years. Each of the events that orbit around the main character of Oghuz Khagan is given in a way that reveals the power of the power. It still remains controversial who was Oghuz Khagan and if he actually lived. However, the most common opinion points out the great ruler of the Huns, Mete Khan. Managing to gather all Turkic clans who lived in Asia under his ruling, Mete Khan resemles Oguz Khagan, particularly with his expansionist character. The ideal of establishing a world power is supported by a dynamic strategy. Such that, the revisionist policy of Oghuz who launched raids for annexing new territories follows a gradual course. When available reviews are considered, it seems that they lack dominant approaches of the discipline of international relations. The basic starting point of this article is to evaluate Oghuz Khagan from different perspectives. In this article, the Uighur version of the epic will be considered, and examined within the context of the basic approaches of the discipline of international relations. In order avoid any repetitions, the epic will not be reinterpreted. The power and security phenomena are discussed at level of Oghuz's intentions where military deployment and war techniques are determined through the main hero. While discussing his several encounters, the reasons leading him to conflict are scrutinized. Presence and level of any transformations in his approach to power are reviewed, emphasizing his focus on maximum benefit and radical moves, which bring him closer to being an autocratic leader in certain aspects. His childhood period is not much elaborated, but gives a perspection that a future warrior is trained. The process between the period he becomes a khagan and allocating his land can be understood at the center of his conquests. On the other hand, the evolution of the war into a legacy becomes clear during the handover ceremony. Furthermore, leaving the power to his sons due to aging after concentrating it in his hand underlines a non-negotiable absolute sovereignty. In this manner, the warrior identity of the hero as well as his sense of reign are emphasized. With an emphasis on Oghuz as a strategic hero, the article focuses on what the real war is because the epic is based on wars and expansion. Apart from the factors that can give rise to a war, the dimensions they take in the epic are discussed. Hence, the situations that start a conflict are widely covered whilw the defense abilities of Oghuz who is engaged in many encounters are also addressed. The khagan, who makes reasonable moves with an awareness of the power capacities of various tribes and his enemies, gets the best by knowing their capabilities, being familiar with his opponents and using the time in his favor. He strengthens his hand by examining the target area in advance and making geographic explorations before starting an operation so that he eliminates all unforeseen factors.
Keywords: War; security; power; government; Oguz Kagan Epic; Arts & Humanities - Other Topics